Open University Center of the Pontifical Javeriana University, Colombia - Omayra Parra de Marroquin (Athabasca University Press, 2002)
According to García Canclini (1990) there is the assumption that Colombia is a hybrid society. Upon this standpoint, and within a traditional higher education structure characterized by being fundamentally conventional or campus based, the Open University Center of the Pontificia Universidad Javeriana was created as an education program that breaks with every traditional scheme, which in turn, encourages a new learning pattern. The Open University Center emerges as a "social response" focused on the "here and now" of today's society in Colombia.